Analisis Kualitas Pelayanan Pada Kantor Kelurahan Pejuang Kota Bekasi - Purwantomo, Purwantomo; Irwansyah, Iwan (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research was conducted to obtain an overview of the quality of service at the Bekasi City Pejuang Subdistrict Office, which is provided by service providers (subdistricts) to the community. The purpose of this research is to determine and analyze the quality of service at the Pejuang Village Office, Bekasi City. This research uses descriptive qualitative research methods. Research results: The quality of service at the Pejuang District Office in Bekasi City is still not fully in accordance with the five indicators, namely tangible, reliability, responsiveness, assurance and empathy. To improve service quality, the Pejuang Subdistrict needs to complete service facilities, accommodate complaints from the public and carry out regular evaluations and conduct training for officers in order to achieve the desired service quality. By making these improvements, it is hoped that Pejuang Village can improve the quality of services and also provide a sense of security and comfort for the community.